The media weapon: an analysis of how the Rhodesian Government used the media to handle the polish refugee issue from 1940 to 1950 - Chigume, Obert; Chakawa, Joshua (Midlands State University, 2016)
The Polish community became the worst victims of the Second World War. They found themselves hemmed between the Germans and the Russians. As a result of their desperate position, the Poles found themselves as refugees not only in Europe but also in African countries. Rhodesia was one such recipient of refugees from Poland who were fleeing from the wrath of Nazi Germany. Despite having supported the British in the war, Polish refugees found that they were discriminated against by the British in Rhodesia who feared being overwhelmed by whites who were not of British stock. There were massive attacks on the Polish community in the Rhodesian press but at the same time, care was taken to ensure that differences between members of the white community would remain unknown to the African community who were looked down upon as an inferior race. Rhodesian policies against fellow whites ensured that at the end of the war, the Polish were compelled to return to their country. Those who remained suffered one form of segregation or another. It was this very policy which prevented the creation of a big white community in Rhodesia. The paper relied on published academic works and the Rhodesian press covering the period up to 1950. Most of the sources consulted came from the National Archives of Zimbabwe.